The End of the World and Other Teachable Moments: Jacques Derrida's Final Seminar - Naas, Michael (Perspectives in Continental Philosophy, 2014)
The End of the World and Other Teachable Moments follows the remarkable itinerary of Jacques Derrida's final seminar, The Beast and the Sovereign (2001-2003), as the explicit themes of the seminar, namely, sovereignty and the question of the animal, come to be supplemented and interrupted by questions of death, mourning, survival, the archive, and, especially, the end of the world.